FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN MENTAL DAN PSIKOMOTOR PADA ANAK BATITA GIZI KURANG - Sri Muljati; Heryudarini Heryudarini; Sandjaja Sandjaja; Anies Irawati; Sudjasmin Sudjasmin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
DETERMINANT FACTORS OF MENTAL AND PSYCHOMOTOR DEVELOPMENT ON MALNOURISHED CHILDREN.Background: The study was carried out in Dramaga-Bogor 1998. Dramaga sub-district was agricultural area that had high proportion of malnourished children under 5 years in Bogor. Inadequate nutrient intake on children motivation, playing as well as children's interaction with mothers and environment.Objectives: The study was conducted to examine the determinant factors of Mental Development Index (MDI) and Psychomotor Development Index (PDI) on malnourished children.Methods: The study was cross sectional, subjects were under three years children that had weight for age < 70% median NCHS. Bailey Mental and Motor development were examined by psychologist in Nutrition Research and Development Centre were asked about social economic and caring practices at home with Mothers or caretakers.Results: The results show that age and stimulation that mothers given effect Mental Development Index (MDI) and Psychomotor Development Index (PDI) on malnourished children. The equation for PDI was Y = 43.849 + 9.322 children's age -7.942 mother's age + 0.009 mother's age * the amount of stimulation often given. The equation for MDI was Y = 91.344 + 25.972 children's age -11.217 mother's age + 0.198 mother's age * the amount of stimulation often given. For MDI was 25.7% and for PDI was 9.3% by children's age after controlling mother's age and stimulation that often given. In order to catch the optimal growth and development, the main focus to improve went should only focusing on body growth but also mental and motor development as well.Keywords: malnourished children, growth and development